Digital distribution and online resources for e-Learning: The case of VUCAVU.com. Issue 3 (3rd July 2021) - Collins, Emily
Abstract: Using VUCAVU.com, an independent Canadian online streaming platform, as a case study, this project seeks to address the increasing need for digital solutions to access film and video art across classrooms and library databases in post-secondary institutions amidst the lack of scholarly attention and industry standards within the digital distribution landscape. Through survey and interview data collection, valuable insights from specialized perspectives in the sector, including instructors and librarians across Canada, outline specific prerequisites that must be implemented to offer a sustainable and desirable streaming option for post-secondary institutions. These research findings form a crucial underpinning for future technological developments across emerging, independent streaming platforms, alongside continued consultation and support from the academic community.